2007
DOI: 10.1063/1.2787150
|View full text |Cite
|
Sign up to set email alerts
|

The structures and electrical transport properties of germanium nanowires encapsulated in carbon nanotubes

Abstract: The structures of Ge nanowires are studied by means of geometry optimization method in this paper. As the radii of carbon nanotubes increase, the structures of the Ge nanowires transform from a monoatomic chain to helical and multishell coaxial cylinders. The physical properties, such as density of states, transmission functions, current-voltage (I-V) characteristics, and conductance spectra (G-V) of optimized nanowires sandwiched between two gold contacts are also obtained. The transport properties of a carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 22 publications
2
38
1
Order By: Relevance
“…CNTs have attracted interest not only for their remarkable properties, such as high mechanical strength [8], high thermal and chemical stabilities [9], excellent heat conduction [10], and interesting electrical and electronic properties [11] but also because their hollow interior can serve as a nanometer-sized mold or template in material fabrication. Recently, significant interest has been shown on the filling of CNTs with materials and various investigations were carried out by researchers, such as the study of the transfer characteristics of water confined in CNTs [12], the structural transformation of partially confined copper nanowires inside defected CNTs [13], the structures and electrical transport properties of germanium nanowires encapsulated in CNTs [14], the structural, electronic, and vibrational properties of the finite carbon chains encapsulated inside CNTs [15], etc. These studies have revealed that matter in a confined nanospace might exhibit extraordinary unusual structures and electronic properties, which is quite different from the behavior of their bulk counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CNTs have attracted interest not only for their remarkable properties, such as high mechanical strength [8], high thermal and chemical stabilities [9], excellent heat conduction [10], and interesting electrical and electronic properties [11] but also because their hollow interior can serve as a nanometer-sized mold or template in material fabrication. Recently, significant interest has been shown on the filling of CNTs with materials and various investigations were carried out by researchers, such as the study of the transfer characteristics of water confined in CNTs [12], the structural transformation of partially confined copper nanowires inside defected CNTs [13], the structures and electrical transport properties of germanium nanowires encapsulated in CNTs [14], the structural, electronic, and vibrational properties of the finite carbon chains encapsulated inside CNTs [15], etc. These studies have revealed that matter in a confined nanospace might exhibit extraordinary unusual structures and electronic properties, which is quite different from the behavior of their bulk counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al [15] and Rusznyak et al [32] have found that structure of monatomic chain changes when encapsulated in CNTs. Li et al [14,33] investigated the structures and electrical transport properties of germanium and nickel nanowires encapsulated in CNTs. Motivated by experimental works [16,30] and considered recent theoretical studies [14,33,34], the electronic transport properties of SiMCs with different geometries which were induced by the encapsulation of different CNTs were investigated by applying density-functional theory (DFT) combined with nonequilibrium Green's functions (NEGF).…”
Section: Introductionmentioning
confidence: 99%
“…When curvature radius reduces to 11.34 Å, complete cylindrical layered structures are formed on curving silicene, similar to the structural transition of nanowires in single walled carbon nanotube (SWNT) [42]. Multishell cylindrical structures have been widely observed in confined nanotubes [43], but this kind of structure on the curved surface is different from the previously reported. Both microstructures of nuclei and silicene-silicon van der Waals interactions result in the spiral phenomenon.…”
Section: Resultsmentioning
confidence: 94%
“…Thus, we correct the wrong conclusion presented by Kośmider et al [21] Our conclusion is consistent with that drawn by Li et al from their studies of the structural properties of gold nanoparticles, germanium nanowires within the fixed SWCNTs. [24][25][26] The phenomenon of layered structure is ascribable to the following reason. Because the structure of the SWCNT is cylindrosymmetric plus a small detailed crystal lattice structure, the force field exerted on the argon atom by the SWCNT is a cylindrosymmetric force field plus a small fluctuation.…”
Section: Methodsmentioning
confidence: 99%